Defectos refractivos y su relación con el uso de dispositivos electrónicos en adolescentes de la Ciudadela Nueva Esperanza – Babahoyo, periodo octubre 2024 – abril 2025. - López Flores, Cristhian Jesús (2025)
The present research aims to determine the relationship between the increase in refractive defects and the use of electronic devices in adolescents in the Nueva Esperanza school, Babahoyo, during the period from October 2024 to April 2025. In a context where the use of electronic screens has increased considerably, especially among young people, this research seeks to determine whether there is a direct relationship between prolonged exposure to electronic devices and the increase in visual problems in the Ciudadela Nueva Esperanza, Babahoyo. Around the world, and aggravated by the pandemic, an epidemic of vision disorders related to electronic devices has been on the rise, with refractive errors being the most common in the youth population. Methodology: The study is based on a correlational level design with a quantitative, cross-sectional approach, field study with a deductive method using techniques such as surveys, refraction and direct observation to collect data. The sample under study is made up of 50 adolescents who reside in the area. The results show that a large part of the adolescents surveyed, 56%, use screens in close vision for more than 6 hours a day, followed by 30% who use screens for 4 - 5 hours, which is directly associated with symptoms such as blurred vision, eye fatigue, eye pain and excessive blinking. In addition, the prevalence of refractive errors such as myopia with 40% and astigmatism with 30%, diagnosed with ocular refraction.